2006
DOI: 10.1100/tsw.2006.394
|View full text |Cite
|
Sign up to set email alerts
|

Update on Robotic Laparoscopic Radical Prostatectomy

Abstract: The da Vinci surgical robot has been shown to help shorten the learning curve for laparoscopic radical prostatectomy (LRP) for both laparoscopically skilled and naïve surgeons[1,2]. This approach has shown equal or superior outcomes to conventional laparoscopic prostatectomy with regard to ease of learning, initial complication rates, conversion to open, blood loss, complications, continence, potency, and margin rates. Although the data are immature to compare oncologic and functional outcomes to open prostate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…7,8 Ahlering et al also reported that a laparoscopically naïve yet experienced open surgeon using a robotic interface successfully transferred open surgical skills to a laparoscopic environment in 8-12 cases. 3 These reports, however, were based on operations carried out by well experienced open surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Ahlering et al also reported that a laparoscopically naïve yet experienced open surgeon using a robotic interface successfully transferred open surgical skills to a laparoscopic environment in 8-12 cases. 3 These reports, however, were based on operations carried out by well experienced open surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Matsunaga et al. [13] reported that the initial experience and training seemed to be accelerated in the case of experienced open surgeons and that robotic assistance enabled both laparoscopically skilled and naive surgeons to achieve operative times similar to an accomplished standard laparoscopist within ≈20 cases.…”
Section: Discussionmentioning
confidence: 99%
“…In urology, most of the reports demonstrated easy adaptation and shorter learning curve in robot-assisted surgery compared with laparoscopic surgery [16][17][18]. Robotic assistance allowed suturing and dexterity skills to be performed faster than laparoscopic assistance.…”
Section: Discussionmentioning
confidence: 99%